Fox Point's own Gemma Hopper - Spangler, Brie (Alfred A. Knopf, 2023)
In Fox Point, Rhode Island, middle schooler Gemma Hopper's older brother, Teddy, is a baseball star. Gemma wishes she could shine on the baseball field too, but she knows it's impossible because with her mom gone and her dad working overtime, Gemma is responsible for taking care of the house and her brothers. Every afternoon, Gemma takes the mound to pitch for her brother's batting practice, and when Teddy comes up with a plan that could get them both to the Major Leagues, she starts to imagine a future of her own design. But Gemma starts to worry that going for her dreams could tear her family apart.